Studies on Collar Rot of Teak Seedlings - Ali, M. I. Mohamed; Florence, E. J. M. (Indian Forester, 1994)
Collar rot of teak (Tectona grandis), a serious nursery disease caused by Rhizoctonia solani anamorph of Thanatephorus cucumeris is recorded for the first time from Kerala. The disease was usually prevelant during the monsoon (July-September). In-vitro fungicidal evaluation against R. solani indicated that carbendazim, thiophanate methyl, carboxin and methoxyethyl mercury chloride were effective in inhibiting the fungal growth and, therefore, may be used in controlling the disease.